Tindak Pidana Pencucian Uang Koperasi Simpan Pinjam: Studi Putusan MA 2113 K/PID.SUS/2023 - Freya Nirmala Natahamidjaja; Ernu Widodo; Nur Handayati (Penerbit Goodwood, 2024)
Purpose: The purpose of this study is to analyze criminal liability for Criminal Acts by Savings and Loan Cooperatives and the application of sanctions by the panel against Criminal Acts in Savings and Loan Cooperatives in the Supreme Court Decision Number 2113 K/PID. SUS/2023. Research Methodology: The type of research is normative juridical with the Statue Approach and Case Study Approach. The data collection method was based on the literature and used a descriptive deductive legal material analysis. Results: Criminal liability for Money Laundering by the Savings and Loan Cooperative carried out by HS has fulfilled the concept of corporate criminal liability of the Identification and Strict Liability theory where HS deserves to be given a criminal sanction of 18 years in prison and a fine of IDR 15,000,000,000. The Supreme Court Decision Number 2113 K / PID.SUS / 2023 is still not appropriate where HS should be subject to additional criminal penalties in accordance with Article 7 of Law No. 8 of 2010 in the form of a maximum fine of IDR 100,000,000,000 or in accordance with Article 121 of Law Number 1 of 2023 in the form of a maximum imprisonment of 20 years, the maximum fine for Corporations is category VIII or IDR 50,000,000,000 Limitations: This study only focuses on discussing the case of money laundering by the Savings and Loan Cooperative in the Supreme Court decision Number 2113 K/PID.SUS/2023 Contributions: This research can be a means of education in analyzing money laundering cases by Savings and Loan Cooperatives in accordance with existing laws and regulations.